2006
DOI: 10.1159/000088288
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Monocyte HLA-DR Expression in the Identification of Early-Onset Neonatal Infection

Abstract: Background: This study aimed to evaluate the diagnostic utilities of monocyte HLA-DR as an infection marker in the identification of early-onset clinical infection and pneumonia in newborn infants. Methods: Term newborns in whom infection was suspected when they were <72 h of age were eligible for enrollment in the study. C-reactive protein (CRP), monocyte HLA-DR and neutrophil CD64 expressions were quantitatively measured at the time of sepsis evaluation (0 h) and 24 h afterwards by flow cytometry and standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
4
26
1
Order By: Relevance
“…In another study, Ng et al demonstrated no significant difference between infected and non-infected or control groups for mHLA-DR expression [31]. In our study, a trend analysis of mHLA-DR indicated that mHLA-DR was significantly downregulated in non-survivors only at a later stage.…”
Section: Chauhan and Hansasupporting
confidence: 44%
“…In another study, Ng et al demonstrated no significant difference between infected and non-infected or control groups for mHLA-DR expression [31]. In our study, a trend analysis of mHLA-DR indicated that mHLA-DR was significantly downregulated in non-survivors only at a later stage.…”
Section: Chauhan and Hansasupporting
confidence: 44%
“…The sensitivity and specificity of CD11b for diagnosing early-onset neonatal sepsis are 86–100 and 100%, respectively [5,59]. CD64 has a sensitivity ranging between 78 and 96% and a NPV between 89 and 97% [70,71]. Though promising, estimation of cell surface markers is limited by the need for sophisticated equipment and the need to process blood samples rapidly before neutrophils die from apoptosis or the surface antigens are downregulated [72].…”
Section: Crp In the Era Of ‘Old’ And Other ‘New’ Infection Markersmentioning
confidence: 99%
“…Although mHLA-DR was downregulated in non-survivors of sepsis at the very onset, nonsurvivors were significantly younger than survivors, but no adjustment for multivariate analysis had been done (18), whereas variation of mHLA-DR with postnatal age is documented (25). On the other hand, Ng et al demonstrated no significant difference in mHLA-DR expression between infected and non-infected or control groups (16). In this study, a trend analysis of mHLA-DR indicated that mHLA-DR was significantly downregulated in non-survivors only at a later stage, i.e., days 4-6 (Supporting Information content 4 and Fig.…”
Section: Ratio Of Neutrophilic Cd64 and Monocytic Hla-drmentioning
confidence: 97%
“…On the other hand, decreased expression of HLA-DR molecules on circulating monocytes has been associated with an anti-inflammatory immune response, referred to as "immunoparalysis" in sepsis (14,15). While the diagnostic significance of HLA-DR is limited (16), a decrease in HLA-DR on monocytes has been associated with deaths in adults (17) and newborn infections (18,19).…”
Section: Introductionmentioning
confidence: 99%